Technological Change, Entry and Stock Market Dynamics: An Analysis of Transition in a Monopolistic Economy - Bipasa Datta; Huw D. Dixon (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper explores an equilibrium model for industry entry dynamics and technological change. We focus on the share valuation of firms in the transition as technology changes, and whether or not share prices are always increasing when technology improves. We find that there can be a U-shaped transition dynamic, so that an initial boom in share price is followed by a temporary fall in share price even though the underlying technology is improving.
Keywords: D40; D92; L10; O30; 330; technology; share-price; entry; industry; dynamic.